Prognosis after curative resection for stage IA gastric cancer in elderly patients: endoscopic submucosal dissection versus surgery - Miyahara, Koji; Ishida, Michihiro; Kono, Yoshiyasu; Hirata, Tetsu; Obayashi, Yuka; Gotoda, Tatsuhiro; Ninomiya, Yuki; Moritou, Yuki; Kunihiro, Masaki; Kubota, Tetsushi; Choda, Yasuhiro; Shirakawa, Yasuhiro; et al. (Surgery today (Tokyo, Japan), 2022)
Purpose To establish whether gastrectomy for early gastric cancer (EGC) in elderly patients is related to poor survival. Methods The subjects of this retrospective study were patients aged ≥ 75 years with primary stage IA EGC, who underwent curative resection with endoscopic submucosal dissection (ESD) or surgery. Results We analyzed data on 365 patients who underwent ESD and 170 patients who underwent surgery. Overall survival (OS) was not significantly different for the ESD group vs. the surgery group (5-year cumulative rates, 81.5% vs. 79.7%; log-rank test, P = 0.506). Multivariate analysis revealed that treatments; namely, ESD or surgery, were not associated with OS (hazard ratio 1.09, 95% confidence interval 0.77–1.51). Similar results were observed even in the subgroups with worse conditions, such as age > 80 years, Eastern Cooperative Oncology Group performance status 2–3, Charlson comorbidity index ≥ 2, and prognostic nutritional index ≤ 46.7. Using propensity score matching, we selected 88 pairs of patients who underwent ESD or surgery with baseline characteristics matched and found that OS was not different between the two groups (log-rank test, P = 0.829). Conclusion OS was comparable for elderly patients who underwent ESD and those who underwent surgery for EGC. Surgical invasiveness did not worsen the prognosis, even for elderly patients.